Chromosomal Microarray Analysis on Intergenerational Effects of Oligomeric Proanthocyanidins Against Bisphenol-A Induced Brain Deformities - Osman, Fatin Naziha; Zakaria, Fatin Nadzirah; Zulazlan, Siti Aishah; Hashim, Nooraain; Dasiman, Razif; Hashim, Nina Keterina (KnE Life Sciences, 2021)
Oligomeric Proanthocyanidins (OPC) is a type of polyphenolic compound which have been demonstrated to have anti-cancer, anti-oxidant, anti-inflammatory and anti-mutagenic properties that may have the potential to reduce intergenerational effect of BPA towards DNA. This study was conducted to determine the effect of OPC on the DNA damage of BPA-induced rats using microarray CGH Chromosome Karyotyping. Adult Male Sprague Dawley rats were divided into six groups which are Normal, BPA, OPC10, OPC20, BPA+OPC10 and BPA+OPC20. The administration of BPA and/or OPC were conducted for 21 days using oral gavage before being mated with female rats of the same age at 1:1 mating ratio. Once the female rats were confirmed pregnant, the male rats were decapitated and their blood were collected for chromosome microarray analysis. The male offspring (F1 generation) were allowed to grow until 10 weeks old and their blood were also collected for chromosome microarray analysis. BPA group had a deletion of Vomeronasal receptor genes in which the deletion magnitude increased from P to F1 generation may affect the ability of the rats to detect chemosensory cues during neurobehavioral test. The amplification of Major Histocompatibility complex (MHC) class I gene in BPA+OPC20 group may aid in a better performance during hippocampal-dependent memory tests. These results suggested that OPC could be a potential agent in reducing the intergenerational effect of BPA. Current finding may enrich our understanding particularly in the possible mechanism of OPC on BPA-induced memory impairment Keywords: Bisphenol-A, Brain, microarray CGH Chromosome Karyotyping, Oligomeric Proanthocyanidins, Intergenerational